Rank Protein Immunolabeling during Bone-Implant Interface Healing Process - Francisley Ávila Souza; Thallita Pereira Queiroz; Eloá Rodrigues Luvizuto; Renato Sussumu Nishioka; Idelmo Rangel Garcia-JR; Paulo Sérgio Perri de Carvalho; Roberta Okamoto (Hindawi Limited, 2010)
The purpose of this paper was to evaluate the expression of RANK protein during bone-healing process around machined surface implants. Twenty male Wistar rats, 90 days old, after having had a 2 mm diameter and 6 mm long implant inserted in their right tibias, were evaluated at 7, 14, 21, and 42 days after healing. After obtaining the histological samples, slides were subjected to RANK immunostaining reaction. Results were quantitatively evaluated. Results. Immunolabeling analysis showed expressions of RANK in osteoclast and osteoblast lineage cells. The statistical analysis showed an increase in the expression of RANK in osteoblasts at 7 postoperative days and a gradual decrease during the chronology of the healing process demonstrated by mild cellular activity in the final stage (P<.05). Conclusion. RANK immunolabeling was observed especially in osteoclast and osteoblast cells in primary bone during the initial periods of bone-healing/implant interface.